Applying Existing Particle Paradigms to Inhaled Microplastic Particles - Wright, Stephanie; Borm, Paul J. A. (Frontiers in Public Health, 2022)
Ambient particulate pollution originating from plastic contaminates air, including indoor and urban environments. The recent discovery of ambient microplastic (MP) particles of a size capable of depositing in the thoracic region of the airway, if inhaled, has raised concern for public exposure and health impacts following lessons learned from other particle domains. Current microplastic exposure estimates are relatively low compared to total ambient particulate matter, but optimal analytical techniques and therefore data for risk and health impact assessments are lacking. In the absence of such an evidence base, this paper explores paradigms, metrics and dose-response curves developed in other particle domains as a starting point for predicting whether microplastic are of concern. Bio-persistence, presence of reactive sites and soluble toxicants are likely key properties in microplastic toxicity, but these are not measured in environmental studies and hence are challenging to interpret in exposure. Data from a MP inhalation study in rats is available but the study was conducted using conditions that do not replicate the known human health effects of PM2.5 or surrogate exposures: compromised, aged animal models are recommended to investigate potential parallels between MPs and PM2.5. One of these parallels is provided by tire wear particles (TWP), which form part of current ambient PM and are sometimes regarded as microplastic. A connection to epidemiological studies where PM filters are still available is recommended and consequently analytical advances are required. In summary, established particle domains and existing paradigms provide valuable insight and data that can be used to predict MP toxicity, and direct study design and key properties to consider in this emerging field.